Advances in Measurement in School-Wide Positive Behavioral Interventions and Supports. (February 2019) - McIntosh, Kent; Lane, Kathleen Lynne
In recent years, there has been an increased research focus on developing tools to support the design, installation, and evaluation of tiered systems of support. In this special issue, we focus on research validating freely available tools to (a) measure fidelity of implementation of school-wide positive behavioral interventions and supports (SWPBIS), (b) assess staff commitment to implement SWPBIS, (c) inform development of teaching matrices, (d) examine issues of sustainability, and (e) assess school climate.